We monsters = Wir Monster [videorecording (DVD)] - Ko, Sebastian; Nebbou, Mehdi; Tscharre, Ulrike C.; Fautz, Janina (First Run Features, 2015)
After their teenage daughter Sarah confesses to the killing of her best friend Charlie, the recently separated Paul and Christine decide to hide the crime. Their collective guilt forces the family back together, creating a web of lies and deadly intentions with no way out.